University proceedings. Volga region. Natural sciences - G.K. Zvereva (Известия высших учебных заведений. Поволжский регион: Естественные науки)
Background. The assimilatory parenchyma of grasses inflorescence plays a major role in the formation of grains. The purpose of the study was to reveal peculiarities of chlorenchyma structure and spatial configurations of assimilatory cells of generative organs of Oryza sativa and Phragmites australis, having, respectively, bambusoid and arundinoid types of leaf anatomy. Materials and methods. The anatomical structure of the chlorenchyma of the lemmas and primary branches in the middle part of the panicle in generative shoots of O. sativa and P. australis fixed in Gammalund’s mixture was studied. The projections of assimilatory cells and their mutual arrangement were examined on transverse and longitudinal sections under a light microscope. Results. Chlorenchyma of flower glumes of O. sativa consists of densely arranged cells of cylindrical shape and cellular second group cells of 2–4 sections. In the floral glumes of P. australis the assimilative tissue is represented mainly by cells elongated along the organ and more diverse variants of cellular cells of the second group. In the axes of the O. sativa panicle, the chlorenchyma cells are loosely arranged and have predominantly lobular-lobed outlines in cross sections; among them, flat and three-dimensional lobular and cellular-lobular cells can be distinguished. The assimilative parenchyma of P. australis inflorescence axes is represented mainly by flat cellular and cellular-lobed cells of the first group. Conclusions. Different parts of inflorescences of O. sativa and P. australis differ in the structure of chlorenchyma and basic three-dimensional forms of assimilation cells. The greatest distribution of assimilation cells of complex shape is observed in the branches of the panicle compared to the flower glumes.